2018
DOI: 10.1007/s10157-018-1617-8
|View full text |Cite
|
Sign up to set email alerts
|

Age- and height-adjusted total kidney volume growth rate in autosomal dominant polycystic kidney diseases

Abstract: MIC is a good renal prediction model applicable to Japanese patients also. AHTKV-α can be a more sensitive and reliable indicator in TKV growth rate than HtTKV slope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Subgrouping using K = 150 does not decrease the role of predicting the rate of estimated glomerular filtration rate decline and enriching the design in clinical trials, because a small change in eHTKV-α does not affect subgrouping limits seriously. 11 , 12 , 19 , 20 However, because eHTKV-α (K = 150) changed significantly from baseline as age advanced in placebo-assigned and standard-of-care subjects ( Table 3 ), it will affect estimations of change in the HTKV growth rate (eHTKV-α) from baseline to postbaseline.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Subgrouping using K = 150 does not decrease the role of predicting the rate of estimated glomerular filtration rate decline and enriching the design in clinical trials, because a small change in eHTKV-α does not affect subgrouping limits seriously. 11 , 12 , 19 , 20 However, because eHTKV-α (K = 150) changed significantly from baseline as age advanced in placebo-assigned and standard-of-care subjects ( Table 3 ), it will affect estimations of change in the HTKV growth rate (eHTKV-α) from baseline to postbaseline.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that eHTKV-α (K = 150) was higher in subjects with PKD1 mutation than in subjects with PKD2 mutation. 11 An association of a higher growth rate of HtTKV with higher risk of disease progression can be identified using eHTKV-α.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Limited data suggest the possibility of faster renal progression in Asian patients with chronic kidney disease (CKD) compared with the Western population 9–11. However, previous studies on Asian ADPKD populations were conducted in a single country, which under-represented the whole Asian ADPKD population 12–27. Moreover, to date, studies that identified patients with ADPKD with rapid progression were mostly conducted in the Western population 5 28–30.…”
Section: Introductionmentioning
confidence: 99%